129k views
0 votes
Solve the system by the elimination method:

-6x + 5y = -11
6x - 11y = -19
A (6,5)
B (-6,-5)
C (5,6)
D (-5, -6)

User Argee
by
4.8k points

1 Answer

2 votes

Answer:

x = 6, y = 5

Explanation:

Solve the following system:

{5 y - 6 x = -11 | (equation 1)

{-11 y + 6 x = -19 | (equation 2)

Add equation 1 to equation 2:

{-(6 x) + 5 y = -11 | (equation 1)

{0 x - 6 y = -30 | (equation 2)

Divide equation 2 by -6:

{-(6 x) + 5 y = -11 | (equation 1)

{0 x + y = 5 | (equation 2)

Subtract 5 × (equation 2) from equation 1:

{-(6 x) + 0 y = -36 | (equation 1)

{0 x + y = 5 | (equation 2)

Divide equation 1 by -6:

{x + 0 y = 6 | (equation 1)

{0 x + y = 5 | (equation 2)

Collect results:

Answer: {x = 6, y = 5

User Banbh
by
4.8k points